1995
DOI: 10.1128/jcm.33.3.528-534.1995
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory power of three DNA-based typing techniques for Pseudomonas aeruginosa

Abstract: We assessed the capacity of three DNA typing techniques to discriminate between 81 geographically, temporally, and epidemiologically unrelated strains of Pseudomonas aeruginosa. The methods, representing powerful tools for hospital molecular epidemiology, included hybridization of restricted chromosomal DNA with toxA and genes coding for rRNA (rDNA) used as probes and macrorestriction analysis of SpeI-digested DNA by pulsed-field gel electrophoresis. The probe typing techniques were able to classify all strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
72
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(82 citation statements)
references
References 33 publications
7
72
0
3
Order By: Relevance
“…While the antibiotic susceptibility patterns appeared more discriminative than the genotypic methods, antibiotic susceptibility testing has relatively limited utility in epidemiological studies because antibiotic resistance is affected by extraordinary selective pressure in contemporary hospitals. Our results providing evidence of genotypic heterogeneity of multidrug-resistant P. aeruginosa O:12 outbreak isolates are in agreement with those reported by Grundmann et al (10). However, these authors did not look at random PCR (10).…”
Section: Environmental Surveysupporting
confidence: 93%
“…While the antibiotic susceptibility patterns appeared more discriminative than the genotypic methods, antibiotic susceptibility testing has relatively limited utility in epidemiological studies because antibiotic resistance is affected by extraordinary selective pressure in contemporary hospitals. Our results providing evidence of genotypic heterogeneity of multidrug-resistant P. aeruginosa O:12 outbreak isolates are in agreement with those reported by Grundmann et al (10). However, these authors did not look at random PCR (10).…”
Section: Environmental Surveysupporting
confidence: 93%
“…Pulsed-field gel electrophoresis (PFGE). Chromosomal DNA was prepared by the procedure of Grundmann et al (10) and digested overnight with 10 U SpeI (Takara Bio, Inc., Shiga, Japan). The DNA fragments were separated on 1.0% agarose gels in 0.5ϫ Tris-borate-EDTA buffer with a CHEF Mapper system (Bio-Rad Laboratories, Hercules, CA) at 6 V/cm for 20 h. The obtained fingerprinting patterns, normalized to the molecular weight markers, were analyzed by the unweighted-pair-group method with Molecular Analyst Fingerprinting Plus software, version 1.6 (Bio-Rad Laboratories, Inc.), to obtain average linkagebased dendrograms.…”
mentioning
confidence: 99%
“…As we have found in our studies (data not shown), most strains from the same hospital generally share the same biochemical profiles and similar antibiograms. In contrast, molecular typing methods including ribotyping have contributed significantly to a better understanding of the epidemiology of P. aeruginosa infections (9,12,16,26).…”
Section: Discussionmentioning
confidence: 99%
“…Diverse DNA-based typing methods have recently been used to fingerprint P. aeruginosa isolates (9), particularly, restriction endonuclease analysis of genornic DNA (21), macrorestriction analysis of digested DNA by pulsefield gel electrophoresis (29), and AP-PCR (12,17,20), and several comparisons of phenotypic and genotypic methods for typing clinical (16,26) or environmental (1 3) strains of P. aeruginosa have been published. Ribotyping has also been successfully used for the typing of various medically important microorganisms (3), including P. aeruginosa (2, 8, 10).…”
mentioning
confidence: 99%